2013
DOI: 10.1128/jb.00921-13
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Function of YciM, a Heat Shock Membrane Protein Required To Maintain Envelope Integrity in Escherichia coli

Abstract: The cell envelope of Gram-negative bacteria is an essential organelle that is important for cell shape and protection from toxic compounds. Proteins involved in envelope biogenesis are therefore attractive targets for the design of new antibacterial agents. In a search for new envelope assembly factors, we screened a collection of Escherichia coli deletion mutants for sensitivity to detergents and hydrophobic antibiotics, a phenotype indicative of defects in the cell envelope. Strains lacking yciM were among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 51 publications
1
36
0
Order By: Relevance
“…The lapB gene was found to be essential at 37°C, and depletion of LapB was shown to cause accumulation of LpxC and increase in LPS amounts, which supports our results. In another study, the lapB mutant was identified in a screen of an E. coli genomic knock-out library (ASKA library), on the basis of its sensitivity to various antibiotics (66). The sensitivity of lapB (yciM) mutants toward antibiotics had already been shown in an earlier study using the same deletion library (68).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The lapB gene was found to be essential at 37°C, and depletion of LapB was shown to cause accumulation of LpxC and increase in LPS amounts, which supports our results. In another study, the lapB mutant was identified in a screen of an E. coli genomic knock-out library (ASKA library), on the basis of its sensitivity to various antibiotics (66). The sensitivity of lapB (yciM) mutants toward antibiotics had already been shown in an earlier study using the same deletion library (68).…”
Section: Discussionmentioning
confidence: 96%
“…During the revision process of this manuscript, three groups described characterization of the lapB gene (yciM) in E. coli and its homolog in Neisseria meningitidis (65)(66)(67). In one study, the lapB (yciM) gene was identified by serendipity, whereby the lapB deletion strain in the ASKA library carried a suppressor mutation in the lpxC gene (65).…”
Section: Discussionmentioning
confidence: 99%
“…In the heteroresistant strain from patient E, a mutation leading to an amino acid substitution encoded within the yciM gene was found. In Escherichia coli, yciM contributes to cell wall integrity by regulating LPS biosynthesis (46,47), and a deletion in yciM leads to decreased susceptibility to colistin (48). It is possible that the mutation in yciM in K. pneumoniae increases LPS production, leading to higher levels of LPS in the outer membrane, which could titrate out the destabilizing effect of colistin binding to LPS.…”
Section: Discussionmentioning
confidence: 99%
“…LapB contains three major structural motifs: the N-terminal transmembrane helix, several tetratricopeptide repeats (TPR), and a C-terminal rubredoxin metal binding domain (Nicolaes et al, 2014). The N-terminal transmembrane helix anchors LapB to the inner membrane of Gram-negative bacteria with the soluble domain in the cytoplasm (Nicolaes et al, 2014).…”
Section: Introductionmentioning
confidence: 99%